Legacy of secrets - Adler, Elizabeth (Elizabeth A.) (New York : Delacorte Press, 1993)
The wildly tangled fortunes of the doughty O'Keefe boys and exquisite Lily of the titled Molyneux family are revealed--Arabian Nights fashion--by ancient Maudie Molyneux in Connemara, Ireland.
Keywords: Connemara (Ireland) -- Fiction; Romantic suspense novels